A single sequential snake saphenous vein graft versus separate left and right vein grafts in coronary artery bypass surgery: a population-based cohort study from the SWEDEHEART registry. (5th March 2019) - Wallgren, Sara; Nielsen, Susanne; Pan, Emily; Pivodic, Aldina; Hansson, Emma C; Malm, Carl Johan; Jeppsson, Anders; Wallinder, Andreas
Abstract: OBJECTIVES: Our goal was to compare short- and midterm outcomes after coronary artery bypass grafting (CABG) using 2 different revascularization strategies. METHODS: A total of 6895 patients were included who had CABG in Sweden from 2009 to 2015 using the left internal mammary artery to the left anterior descending artery and either a single sequential saphenous vein graft connecting the left and right coronary territories to the aorta (snake graft, n = 2122) or separate vein grafts to both territories ( n = 4773). Data were obtained from the Swedish Web System for Enhancement of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies (SWEDEHEART) and the Swedish Patient Registry. The groups were compared using adjusted logistic regression for short-term (30-day) and Cox regression and flexible parametric survival models for midterm outcomes. Primary outcome was a composite of all-cause mortality, myocardial infarction (MI), reangiography and new revascularization. The median follow-up time was 35 months. RESULTS: At 30 days, the incidences of the composite end point [odds ratio (OR) 1.31, 95% confidence interval (CI) 1.03–1.68; P = 0.03] and reangiography (OR 1.51, 95% CI 1.07–2.14; P = 0.02) were higher in the snake group. There was also a trend towards higher mortality (OR 1.47, 95% CI 0.97–2.22; P = 0.07). The event rates during the complete follow-up period were 6.5 (5.9–7.2) and 5.7 (5.3–6.1) per 100 person-years for the snake group and the separate vein group, respectively. At the midterm follow-up, no significant difference between the groups could be shown for the composite end point [hazard ratio (HR) 1.08, 95% CI 0.95–1.22; P = 0.24], mortality (HR 0.95, 95% CI 0.79–1.14; P = 0.56), MI (HR 1.11, 95% CI 0.88–1.41; P = 0.39) or new revascularization (HR 1.19, 95% CI 0.94–1.50; P = 0.15), whereas reangiography remained more common in the snake group (HR 1.25, 95% CI 1.05–1.48; P = 0.01). CONCLUSIONS: Snake grafts were associated with a higher rate of early postoperative complications, possibly reflecting a more demanding surgical technique, whereas midterm outcomes were comparable. Based on these data, one strategy cannot be recommended over the other.